Sandwich square honeycomb structure from biodegradable and recyclable composites - Zahidah, Ansari (2018)
Increasing environment concern has triggered the development of natural fibre composite, especially in a honeycomb structure due to its lightweight properties. A honeycomb structure is usually used in aerospace, automotive and recently in furniture industries as it is a good weight saving option. However, only a small number of natural fibre composites have been studied as a honeycomb structure. Besides that, the prospect of recycling the natural fibre composite into a new product has yet to be discussed in any previous research. This research aims to investigate the mechanical properties of the sandwich square honeycomb structure made out of three types of fibre, which are kenaf, pineapple and sugar palm fibre reinforced with polylactic acid (PLA). Apart from that, the objectives of this study are to study the compression behaviour, the scaling effect and the finite element analysis of the sandwich square honeycomb structure. Furthermore, this research also investigates the effect of recycling the natural fibre composite in term of its strength and energy absorption values. This study was conducted on natural fibre composites made from mixing PLA with three different types of natural fibres; kenaf, sugar palm and pineapple leave fibres. The long fibres were crushed and sieved into short fibres to ensure uniformity throughout the process including recycling. Then fibres and PLA were mixed using a batch mixer at 180ºC before being crushed into small pallets for the hot press moulding. Hot pressing the pallets in a designated mould for 5 minutes at 180 º C and 60 tonnes of pressure produced plates of each fibre with a thickness of 3 mm. Later on, the plate underwent tensile test and the sandwich square honeycomb structure fabricated from the plate underwent a compression test. The end products were then recycled into plates by the same process of crushing into pallets, hot pressing and fabrication into sandwich square honeycomb structure without adding any new materials. The recycled sandwich square honeycomb were also put through the same set of tensile and compression test in order to investigate the strength and energy absorption capabilities. Tensile strength of kenaf/PLA composite recorded the highest value of 36.28 MPa for new composite and 19.72 MPa for recycled composite. After the recycling process, the tensile strength exhibit a reduction between 5-45 %. The Poisson’s ratio of the composite both new and recycled was also recorded between 0.2-0.3, which is the normal range for natural fibre composites. Besides that, in term of scaling factor, the value of compression stress and energy absorption increased when the number of cell increased. The sugar palm/PLA indicated the highest increment of 115.20% when the number of slots doubled. Meanwhile, FE model was developed and analysed using ABAQUS 6.13 software to verify the experimental results obtained. However, when the natural fibre composite was recycled, kenaf/PLA recycled composite recorded the highest maximum stress of 7.8 MPa and energy absorption value of 720.12 J compared to recycled pineapple/PLA and sugar palm/PLA composite. Finally, the comparison between the FE model and experimental data presented a small percentage error of 10.97 % due to the geometries’ imperfections of the experimental sandwich square honeycomb structures. This showed that the recycled natural fibre composite has a good possibility to be used to replace current materials in low load bearing application especially in furniture making industry.